2022
DOI: 10.1186/s12877-022-03380-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diet quality and depression among Iranian older adults in Tehran

Abstract: Background Depression is one of the prevalent mental disorders that is common in older ages. Evidence suggests that dietary intake status may potentially be associated with depression. However, this association has not been well studied in older adults, and the nature of the association remains unclear. This study aimed to investigate the association between diet quality and depression in free-living older adults living in Tehran city. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In analyzing the association between 13 specific food groups and the risk of depression symptoms, our results in the older adults are broadly consistent with previous literature. A cross-sectional survey from Iran showed an 82.4 % lower risk of depression symptoms in the third quartile compared to older adults in the first quartile of the HEI (OR = 0.176; 95 % CI: 0.020 to 1.524) after adjusting for all potential confounders, but no statistical significance was observed, possibly related to the small sample size of the study ( Chegini et al, 2022 ). In another study, Wang et al ( Wang et al, 2021 ) analyzed data from the National Health and Nutrition Examination Survey and found that after multivariate adjustment, average HEI (OR = 0.848; 95 % CI: 0.846 to 0.849) and optimal HEI (OR = 0.455; 95 % CI: 0.453 to 0.456) were associated with reduced odds of depression symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…In analyzing the association between 13 specific food groups and the risk of depression symptoms, our results in the older adults are broadly consistent with previous literature. A cross-sectional survey from Iran showed an 82.4 % lower risk of depression symptoms in the third quartile compared to older adults in the first quartile of the HEI (OR = 0.176; 95 % CI: 0.020 to 1.524) after adjusting for all potential confounders, but no statistical significance was observed, possibly related to the small sample size of the study ( Chegini et al, 2022 ). In another study, Wang et al ( Wang et al, 2021 ) analyzed data from the National Health and Nutrition Examination Survey and found that after multivariate adjustment, average HEI (OR = 0.848; 95 % CI: 0.846 to 0.849) and optimal HEI (OR = 0.455; 95 % CI: 0.453 to 0.456) were associated with reduced odds of depression symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, investigations by Saneei et al ( 41 ) assessed the HEI in relation to metabolic syndrome and diabetes risk in the Iranian population, conditions that have been linked to an increased risk of depression ( 42 ). Moreover, Chegini et al examined the relationship between HEI and mental health outcomes among Iranian older adults, suggesting that adherence to a higher HEI was associated with a reduced risk of major depression ( 43 ). Overall, these studies collectively underscore the significance of the Healthy Eating Index as a valuable tool for assessing dietary quality and its impact on various health outcomes, including major depression, in the Iranian population.…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized, double-blind, placebo-controlled clinical trial focusing on adolescents who consumed a daily supplement of wild blueberry (containing approximately 253 mg anthocyanidins) found that compared to the placebo group, participants receiving anthocyanidin supplements had significantly reduced self-reported depressive symptoms (P = 0.02, 95%CI: (-6.71,-5.35)] [28]. Previous cross-sectional studies have also demonstrated that correlation between higher diet quality, as indicated by higher scores on the Healthy Eating Index HEI2015), and a lower risk of depression [29][30][31]. Our study further confirms this association [46.09 (0.66) vs. 50.85 (0.47), P<0.0001].…”
Section: Table 2 Differences In Flavonoid Content Between the Depress...mentioning
confidence: 99%